Bright Mono‐aqua Europium Complexes Based on Triazacyclononane That Bind Anions Reversibly and Permeate Cells Efficiently. Issue 29 (6th June 2013) - Butler, Stephen J.; McMahon, Brian K.; Pal, Robert; Parker, David; Walton, James W.
Abstract A series of five europium(III) complexes has been prepared from heptadentate N5O2 ligands that possess a brightness of more than 10 mM−1 cm−1 in water, following excitation over the range λ=330–355 nm. Binding of several oxy anions has been assessed by emission spectral titrimetric analysis, with the binding of simple carboxylates, lactate and citrate involving a common ligation mode following displacement of the coordinated water. Selectivity for bicarbonate allows the rapid determination of this anion in human serum, with Kd=37 mM (295 K). The complexes are internalised quickly into mammalian cells and exhibit a mitochondrial localisation at early time points, migrating after a few hours to reveal a predominant lysosomal distribution. Herein, we report the synthesis and complexation behaviour of strongly emissive europium (III) complexes that bind oxy‐anions in aqueous media with an affinity and selectivity profile that is distinctively different from previously studied systems.